Just the Facts: Recommendations on point-of-care ultrasound use and machine infection control during the coronavirus disease 2019 pandemic. Issue 4 (July 2020) - Kim, Daniel J.; Jelic, Tomislav; Woo, Michael Y.; Heslop, Claire; Olszynski, Paul
Abstract : The World Health Organization declared the novel coronavirus disease 2019 (COVID-19) to be a pandemic on March 11, 2020, and, currently, there are over 10, 000 confirmed cases in Canada, with this number expected to grow exponentially. There has been widespread interest in the use of point-of-care ultrasound (POCUS) in the management of patients with suspected COVID-19. The CAEP Emergency Ultrasound Committee has developed recommendations on the use of POCUS in these patients, with an emphasis on machine infection control measures.